End of Meeting Report - ISPC 3 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
The third ISPC meeting was attended by 56 participants from 3rd to 4th March 2011. The report annexes contain the list of participants as well as the final agenda for the meeting.